Nanotope™ sebagai Sistem penghantaran Cosmeceutical untuk Meningkatkan Intensitas Efek pada Kulit - Ulma Sintia; Regina Andayani; Henny Lucida (Journal of Pharmaceutical and Sciences, 2023)
Nanotope™ as a monolayer nanoencapsulated vesicular delivery system, consisting of a membrane formed by phospholipids (lecithin) and cosurfactants. Nanotope™ is an Ultra-small Unilamellar Carrier (USUC) having an average globule size of 0-40 nm. The diameter of the globule size which is smaller than the size of the skin pores allows the active ingredients to penetrate the stratum corneum to reach the target. Natural active compounds such as catechin, alpha mangostin, quercetin, and ascorbic acid have great potential as active ingredients to be formulated in cosmetic preparations. However, these compounds have limited penetration into the skin. Therefore, the Nanotope™ delivery system is the best solution for encapsulating these active ingredients without reducing their effectiveness. Cosmetic serums, creams and emulgel are preparations that are most likely to be formulated with the Nanotope™ delivery system. This review article presents Nanotope™ preparation techniques along with their evaluations, as well as active compounds from natural ingredients that have the potential for cosmetic applications with the Nanotope™ delivery system.